Social worlds of Appalachian women caregivers of older relatives living with dementia - McCann, Brandy Renee; Roberto, Karen A.; Savla, J.; Blieszner, Rosemary (Frontiers in Global Women's Health, 2024)
RationaleOver 11 million people in the United States provide care for an older family member with dementia, with this responsibility primarily falling on daughters and wives. In Appalachia, a mountainous region in the U.S characterized by close families, family members were crucial to ensuring that care needs were met for people living with dementia during the COVID-19 pandemic. However, we know little about the well-being of family caregivers during the public health crisis. Guided by a Limited Future Time Perspective postulate, which posits that as people age they begin to prioritize emotionally meaningful relationships over instrumental goals, we asked how dementia caregiving changes the social lives of family caregivers situated within kin networks; and how a public health crisis (i.e., COVID-19 pandemic) affects caregivers who are already at risk for social isolation and feelings of loneliness.MethodsParticipants were recruited from a regional health care system and four Area Agencies on Aging. In our longitudinal study we invited family caregivers to be interviewed at multiple time points over a 4-year period. The sample for this study was women caregivers interviewed (N = 27; age range 32–81, m = 63). Interviewers followed a semi-structured protocol with questions designed to elicit descriptions about (a) changes in formal and informal support over time, (b) the person living with dementia's symptoms and disease progression, and (c) how the pandemic affected caregivers’ and persons living with dementia's social worlds.FindingsWe found three types of caregivers: (1) caregivers who had social lives interdependent with their relative with dementia, (2) caregivers and persons living with dementia whose social lives were restricted due to dementia symptoms and caregiving demands, and (3) caregivers and their relative living with dementia who maintained separate social lives. Dementia symptoms more than social distancing measures contributed to caregivers’ shrinking social worlds particularly for those with interdependent social lives despite living amongst kin.ConclusionsThis study is important in understanding how women in Appalachia fared during a pandemic in the context of dementia caregiving. This research supports the need for respite services and dementia care training for respite workers.